Los derechos lingûísticos de las comunidades kichwas en las políticas en la provincia de Imbabura - Escola, Carlos F. (2022)
Ecuador, like other countries in Latin America, especially in the Andean region, is going through a linguistic problem, due to the fact that most of its original languages are in danger of extinction; issue that also affects the effective use of these in legislative and regulatory texts, which led to analyze the linguistic rights of the Kichwa communities in public policies in the province of Imbabura, in attention to the fundamental right of respect for the original languages of nationalities and indigenous peoples of this province. For this, an investigation was based on the qualitative approach, of a descriptive legal type and with a documentary design to characterize the Kichwa language as a language in the Ecuadorian legal system. Likewise, a structured interview consisting of 7 questions was applied, addressed to: Judge of the Judicial Unit for Children, Family, Women, Adolescents and Adolescent Offenders; GPI Vice Prefecture; President of the GADSJI; President of the ASM; and Professor at the University of Otavalo. The results of the same made it possible to show that there are public policies aimed at issues such as education, people with disabilities, tourism, among others, where the observance of the criterion of interculturality is unapplied and where the Castilian language remains intact, which violates the right to opportune and due information and the principle of transparency coupled with the necessary intercultural approach. Likewise, it was concluded that there are still no legal provisions or approved Ordinances that regulate and guarantee the continuity and protection of the Kichwa language.